Biomechanical comparison of screw position in variable angle locking plate in intra-articular calcaneal fractures: Cadaveric and radiologic study - Baba, Vit; Capek, Lukas; Kopp, Lubomir; Bittner, Vaclav (Clinical biomechanics (Bristol, Avon), 2025)
BACKGROUND: Lateral plating of calcaneal fractures using variable-angle locking plates is still the golden standard for severely comminuted cases. The aim of this study is to explore the possibilities of improving stability of osteosynthesis by changing screw directions. It provides an assessment and comparison of cadaveric biomechanical experiment with retrospective radiologic data analysis. METHODS: In the cadaveric study 8 intact calcaneus-talus specimens were obtained from 4 deceased donors. Fracture type 2b according to Sanders' classification was created in each specimen and fixed with variable-angle locking plate. The specimens were divided in 2 groups differing in orientation of anterior screws and fixed in PMMA base. A push-in test was performed by a two-column testing machine until gross failure. Retrospective cohort study was performed, reviewing data of 74 patients which underwent surgical treatment of calcaneal fractures with the same construct. Evaluation was performed at scheduled CT and X-Ray controls. Direction of inserted screws and implant failure were noted. FINDINGS: The cadaveric study proved that there is no significant difference in mean failure force between two abovementioned screw configurations in Sanders 2b fracture. A significant difference was observed in initial stiffness. The radiologic retrospective study showed that difference in screw position within all fracture types but type 2b is significant. INTERPRETATION: Screw configuration in the anterior part of variable-angle locking plate appears to affect primary stiffness and stability of the construct. Particularly in more comminuted fractures, screw inserted in the direction of sustentaculum improves the stability and lowers risk of implant failure.
Keywords: Radiography; Cadaveric; Male; retrospektivní studie; Middle Aged; Bone Plates; Fracture Fixation, Internal; vnitřní fixace fraktury; radiografie; Adult; Biomechanical Phenomena; Aged; dospělí; mužské pohlaví; senioři; Calcaneus; Intra-Articular Fractures; Cadaver; biomechanika; kostní šrouby; senioři nad 80 let; lidé; Fracture; ženské pohlaví; Study; kostní destičky; Humans; Failure; Aged, 80 and over; patní kost; Retrospective Studies; Female; fraktury kostí; lidé středního věku; Fractures, Bone; mrtvola; intraartikulární fraktury; Bone Screws